Handbook of CDMA systems design, engineering, and optimization - Kim, Kyoung Il (Prentice Hall PTR, 2000)
Compiles the digital CDMA mobile communications field's most valuable experience and methods in a single authoritative, current resource for every working CDMA professional. CD-ROM included. DLC: Code division multiple access.